(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The purpose of this article is to analyze the origin of the concept of ontotheology in the history of philosophy and its reception in the contemporary Protestant theology. The term «ontotheology» was coined by I. Kant who used it as a designation for the ontological proof of the existence of God based on mere concepts. Kant demonstrated that metaphysical conception of God as supremely perfect being doesn’t provide any knowledge about the reality of God with objective certainty. The further development of the notion of ontotheology was undertaken by M. Heidegger. His usage of the notion of ontotheology is much broader in scope than Kantian. According to Heidegger, ontotheological thinking characterizes entire Western metaphysical tradition for which the question of Being is bound up with the question of the God. However, Heidegger’s critique of ontotheology should not be taken as a critique of theistic discourse as such, a critique that seeks to provide a philosophical case against belief in a Creator. It is a critique of a metaphysical tradition that reduces God to a First Explainer fully intelligible to human understanding. This aspect of the critique of ontotheology was mostly appropriated in contemporary Protestant theology. Key words: Ontotheology, metaphysics, epistemology, I. Kant, M. Heidegger, Protestant theology.